2009
DOI: 10.1016/j.jacc.2009.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spironolactone on Left Ventricular Mass and Aortic Stiffness in Early-Stage Chronic Kidney Disease

Abstract: The use of spironolactone reduces left ventricular mass and improves arterial stiffness in early-stage CKD. These effects suggest that aldosterone exerts adverse cardiovascular effects in CKD and that spironolactone is worthy of further study as a treatment that could reduce adverse cardiovascular events. (Is Spironolactone Safe and Effective in the Treatment of Cardiovascular Disease in Mild Chronic Renal Failure; NCT00291720).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
205
2
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(221 citation statements)
references
References 44 publications
(40 reference statements)
6
205
2
8
Order By: Relevance
“…There are limited data demonstrating the influence of MR antagonism on arterial stiffness in human CKD. The addition of the MR inhibitor spironolactone to ACEI/ARB treatment in stage 2 and 3 CKD patients significantly reduced arterial stiffness and left ventricular mass, supporting the hypothesis that aldosterone is a major mediator of arterial stiffness and left ventricular hypertrophy in CKD [33] . High salt diets also have important role in the development of hypertension and arterial stiffness [34] .…”
Section: Arterial Stiffness In Chronic Kid-ney Diseasementioning
confidence: 60%
“…There are limited data demonstrating the influence of MR antagonism on arterial stiffness in human CKD. The addition of the MR inhibitor spironolactone to ACEI/ARB treatment in stage 2 and 3 CKD patients significantly reduced arterial stiffness and left ventricular mass, supporting the hypothesis that aldosterone is a major mediator of arterial stiffness and left ventricular hypertrophy in CKD [33] . High salt diets also have important role in the development of hypertension and arterial stiffness [34] .…”
Section: Arterial Stiffness In Chronic Kid-ney Diseasementioning
confidence: 60%
“…As aldosterone is part of the progressive fibrosis of the heart, vessels, and kidney, MRA is highly interesting as a possible way of preventing renal fibrosis and reducing cardiovascular complications in patients with CKD 10, 26. A recent meta‐analysis of 12 CKD studies and >4000 patients showed that MRA treatment did benefit CKD patients regarding left ventricular muscular mass, all‐cause mortality, and cardiovascular events with no increased incidence of severe hyperkalemia 27.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chronic kidney disease (CKD) is common in HF and is an important risk factor for worse outcome 8, 9. Even though MRAs have been found to reduce left ventricular mass and arterial stiffness in patients with CKD, CKD is a determinant for MRA use in HF by the risk of worsening renal function and hyperkalemia 10. We lack studies examining outcome of MRA use in unselected MI patients with HF and CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Studying 98 patients in each group would give us a 95% power to detect a difference of 0.4 m s -1 between groups based on our previously published work on arterial stiffness in CKD, 30 where patients had a PWV of 8.3 m s -1 with the s.d. of 1.7 using a two-tailed test at the 5% significance level.…”
Section: Values Are Represented As Means ± Sd or Medians (Interquarmentioning
confidence: 99%